Neural correlates of food labels on brand, nature, and nutrition: An fMRI meta-analysis - Yeung, Andy Wai Kan (Frontiers in Nutrition, 2022)
Eating is an essential act of our everyday life, and it involves complicated cognitive appraisal and gustatory evaluation. This study meta-analyzed the functional magnetic resonance imaging (fMRI) studies about food labels on brand, nature and nutrition. Web of Science Core Collection (WoS), Scopus, and PubMed were queried to identify human fMRI studies written in English and published in peer-reviewed journals and used taste or food related labels. Studies were excluded if they reported no results from taste/food related stimuli versus control, no task-based fMRI results, or no results from whole-brain analysis. Nineteen studies entered the analysis. Results for the meta-analysis on food nutrition revealed that the precuneus on the right hemisphere was significantly activated, a brain region related to internal mentation of self-consciousness and nutritional evaluation. Results for the overall analysis on all 19 studies, the analysis on food brand, and the analysis on food nature revealed no significant brain regions. Food nutrition labels were generally processed by brain regions related to internal mentation of self-consciousness and nutritional evaluation. However, the neural correlates of labels of food brand and food nature were inconsistent across studies. More future studies are needed to better understand the cognitive processing of different kinds of food labels in our brain.